2017
DOI: 10.1039/c7tc02225e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of hole mobility in hybrid titanium dioxide/poly(3-hexylthiophene) nanocomposites by employing an oligothiophene dye as an interface modifier

Abstract: Hole-mobility in nanocrystalline TiO2/P3HT composites is increased by over an order of magnitude when the TiO2 surface is treated with a 3-hexylthiophene oligomer bearing a cyanoacrylic acid group (4T).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…A metal-oxide nanoparticle (TiO 2 , ZnO) percolation network with thickness in the submicron scale provides a stable and transparent backbone network for free carrier transport in this type of solar cells [2]. However, the power conversion efficiency (PCE) of these hybrid devices is limited due to several reasons, including interfacial carrier recombination [3,4] at the interface, poor mobilities in the metal-oxide polymer nanocomposite, and poor spectral response of the polymer [5,6,7,8]. Typically, the nanoporous metal oxides are the electron acceptors and the π-conjugated polymers are the donors [9,10,11] in hybrid metal-oxide polymer solar cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A metal-oxide nanoparticle (TiO 2 , ZnO) percolation network with thickness in the submicron scale provides a stable and transparent backbone network for free carrier transport in this type of solar cells [2]. However, the power conversion efficiency (PCE) of these hybrid devices is limited due to several reasons, including interfacial carrier recombination [3,4] at the interface, poor mobilities in the metal-oxide polymer nanocomposite, and poor spectral response of the polymer [5,6,7,8]. Typically, the nanoporous metal oxides are the electron acceptors and the π-conjugated polymers are the donors [9,10,11] in hybrid metal-oxide polymer solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The electron transfer from a donor into an acceptor produces a large proportion of charge carrier pairs across the donor/acceptor interface. In that situation, the Coulombic attraction of these bound charge carrier pairs limit the device performance by feeding the recombination effects at the interface [8,12,13,14]. It has been shown that engineering the metal-oxide polymer interface can improve the PCE of hybrid solar cells [12,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…6,14,15 In this study, we bound a series of oligothiophene dyes to ZnO NCs through a cyanoacrylate anchoring group ( Figure 1) and measured their excited state electron transfer rates using ultrafast pump-probe spectroscopy. Compounds 3T and 4T are known to be effective interface modifiers in dye-sensitized solar cells, 6,16 and 5T itself has been demonstrated an effective dye for solar cells. 17,18 This series of compounds is of particular interest because, despite large differences in their absorption spectra, the energies of the LUMOs, which are primarily localized on the cyanoacrylate moiety and the adjacent thiophene ring, of 2T, 3T, 4T and 5T were reported to be similar.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 thin film on the ITO substrate was fabricated by simple spray pyrolysis as reported earlier [26,27]. The precursor solution for the spray was prepared as follows.…”
Section: Methodsmentioning
confidence: 99%